2021
DOI: 10.3390/s21020392
|View full text |Cite
|
Sign up to set email alerts
|

FAR-Net: Feature-Wise Attention-Based Relation Network for Multilabel Jujube Defect Classification

Abstract: In production, due to natural conditions or process peculiarities, a single product often may exhibit more than one type of defect. The accurate identification of all defects has an important guiding significance and practical value to improve the planting and production processes. Concerning the surface defect classification task, convolutional neural networks can be implemented as a powerful instrument. However, a typical convolutional neural network tends to consider an image as an inseparable entity and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Arthur et al trained the deep residual neural network (ResNet) classifier to detect the external defects on tomatoes, and they found that fine-tuning outperformed feature extraction, revealing the benefit of training additional layers when sufficient data samples are available [16]. Xu et al proposed a feature-wise attention-based relation network (FAR-Net) for multilabel jujube defect classification, which effectively facilitated the learning of correlation between labels and improved the multilabel classification accuracy [17]. Ahmad et al used an improved CNN algorithm to detect the apparent defects of sour lemon fruit and graded them [18].…”
Section: Introductionmentioning
confidence: 99%
“…Arthur et al trained the deep residual neural network (ResNet) classifier to detect the external defects on tomatoes, and they found that fine-tuning outperformed feature extraction, revealing the benefit of training additional layers when sufficient data samples are available [16]. Xu et al proposed a feature-wise attention-based relation network (FAR-Net) for multilabel jujube defect classification, which effectively facilitated the learning of correlation between labels and improved the multilabel classification accuracy [17]. Ahmad et al used an improved CNN algorithm to detect the apparent defects of sour lemon fruit and graded them [18].…”
Section: Introductionmentioning
confidence: 99%